(untitled) (International journal of artificial intelligence, 2025)
This article discusses the greatest good that can be done to a child, upbringing, which has become one of the most pressing problems today, the shortcomings and problems in raising a person, as well as the causes of these problems, the axiological approach to solving them in a positive way, and the thoughts of our country's thinkers on raising a person.